Profil Asam Lemak Tuna (Thunnus albacares) Loin dengan Penyemprotan Filtered Smoke selama Penyimpanan Beku : The profile of fatty acid of Tuna Loin (Thunnus albacores) sprayed by Filtered Smoke during frozen storage - Cindy Regina Magdalena Loppies; Daniel A.N. Apituley; Raja Bonan Dolok Sormin; Beni Setha; Johanis Hiariej (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
The red color is one of the factors that determining freshness of tuna loin. To keep the red color of the tuna flesh, it has been treated by filtered smoke. Filtered smoke reduces the oxidative of fat as well as keep the fat quality. The objective of this research was to study the fatty acid composition of tuna (Thunnus albacores) loin treated by filtered smoke. The research method was conducted experimentally. Tuna loin firstly sprayed by filtered smoke at a pressure 1 atm for 5 – 10 seconds before storage at freezing temperature -25 ˚C for four weeks. Observations were 0 and 4 weeks and the parameters observed were the fatty acid profiles, atherogenic index (AI), thrombogenic index (TI), fat quality (h / H) and the index of polien. The result showed there were 29 types of fatty acids consisting of 13 types of saturated fatty acids (SFA), 6 types of monounsaturated fatty acids (MUFA) and 11 types of poly unsaturated fatty acids (PUFA). There were indentified as the highest SAFA, MUFA, PUFA for storage time 0 and 4 weeks were palmitic acid (C16: 0) 8.93%; 15.14%, oleic acid (C18: 1n9c) 3.73%; 5.01% and docosahexaenoic acid, (C22: 6n3) 6.77% ; 5.73% respectively. It indicated that the fatty acid of tuna loin were categorized good, where it was indicated by the AI, TI, h/H and polien index for storage time 0 and 4 weeks 1.11; 0.83, 0.50; 0.69, 1.49; 1.72, and 1.49 ; 1.31 respectively.